Voltammetric and amperometric determination of doxorubicin using carbon paste electrodes - Jemelková, Zuzana; Zima, Jiří; Barek, Jiří (Collection of Czechoslovak Chemical Communications, 2009)
Direct current voltammetric (DCV) and differential pulse voltammetric (DPV) determination of antineoplastic agent doxorubicin (DOX) at a carbon paste electrode (CPE) was developed. Britton–Robinson buffer (pH 7.0) was used as a supporting electrolyte. The limits of detection are 8 × 10–7 mol l–1 (DCV) and 6 × 10–8 mol l–1 (DPV). The accumulation of DOX at the electrode surface was used to decrease the limits of detection down to 2.2 × 10–7 mol l–1 for adsorptive stripping DC voltammetry (DCAdSV) and 2.8 × 10–9 mol l–1 for adsorptive stripping differential pulse voltammetry (DPAdSV) at CPE. The results of the voltammetric methods were utilized for the development of a new determination of doxorubicin using HPLC with amperometric detection on CPE based on spherical microparticles of glassy carbon in a wall-jet configuration. A column with chemically bonded C18 stationary phase and a mobile phase containing 0.01 M phosphate buffer (pH 5.0)–methanol 25:75 (v/v) were used. The limit of detection is 4 × 10–7 mol l–1 (HPLC with electrochemical detection (ED)).
Keywords: financování organizované; Doxorubicin; vysokoúčinná kapalinová chromatografie; Financing, Organized; elektrody; Chromatography, High Pressure Liquid; Electrodes; Electrochemistry; doxorubicin; elektrochemie